2016
DOI: 10.35790/ebm.4.2.2016.14611
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan merokok dengan saturasi oksigen pada pegawai di fakultas kedokteran universitas Sam Ratulangi Manado

Abstract: Smoking is an overt behavior in which smokers inhale tobacco rolls. The degree of smoking can be determined based on the Brinkman index. Global Adults Tobacco Survey (GATS) estimates there are currently 7.9 billion adults who are actively smoking and 3.5 billion people are exposed to secondhand smoke in the workplace. This research aims to identify oxygen saturation of smokers and the correlation between smoking and oxygen saturation of administration staffs in the Medical Faculty of Sam Ratulangi University M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
1
0
7
Order By: Relevance
“…A history of smoking has a significant association with decreased oxygen saturation. Research conducted by Septia (2016) explained that in smokers of heavy degrees have an average oxygen saturation of 97% lower compared to light degree smokers who have an average oxygen saturation value of 98.37% so from the study it was concluded that the heavier the degree of smoking, the lower the level of oxygen saturation in the blood (Septia et al, 2016). In active smokers there will be mucus hyper secretion and chronic airway obstruction due to the habit of smokers who smoke harmful Jurnal Kesehatan dr. Soebandi Vol.…”
Section: Discussionmentioning
confidence: 99%
“…A history of smoking has a significant association with decreased oxygen saturation. Research conducted by Septia (2016) explained that in smokers of heavy degrees have an average oxygen saturation of 97% lower compared to light degree smokers who have an average oxygen saturation value of 98.37% so from the study it was concluded that the heavier the degree of smoking, the lower the level of oxygen saturation in the blood (Septia et al, 2016). In active smokers there will be mucus hyper secretion and chronic airway obstruction due to the habit of smokers who smoke harmful Jurnal Kesehatan dr. Soebandi Vol.…”
Section: Discussionmentioning
confidence: 99%
“…Nilai dari saturasi oksigen menunjukkan adanya jumlah kadar oksigen dalam darah, normalnya saturasi oksigen dalam darah adalah 95-100% yangbisa diukur drngan menggunakan alat oksimetri, ketiga saturasi oksigen dalam darah menjadi berkurang maka akan menunjukkan nilai <95%. Ketika nilai saturasi oksigen dalam darah berkurang, maka akan menyebabkan hipoksia pada pasien (Septia et al, 2016). Tujuan utama penatalaksanaan dan pengobatan bagi pasien dengan PPOK peningkatan fungsi otot inspirasi dan mengurangi sesak napas.…”
Section: Pendahuluanunclassified
“…Perubahan pola nafas dan penurunan saturasi oksigen, ini menunjukkan bahwa ada masalah pada organ paru-paru dengan riwayat perokok berat. Ada kaitan yang berarti antara merokok dengan kemampuan paru (Septia, Wungouw, & Doda, 2016). Pada rokok juga terdapat HCN merupakan zat kimia gas yang paling ringan dan mudah terbakar yang dapat menyebabkan hipoksia seluler dengan mengganggu rantai transport elektron sehingga sel tidak dapat lagi memroduksi ATP (secara aerobik) untuk aktifitas sel.…”
Section: Pembahasanunclassified